Body, time and transfiguration - Jesús Alberto Cabañas Osorio (Educación Física y Ciencia, 2009)
Following exposure has as premise; make an x-ray of the time within the human body. An analysis of ways of time and pace inhabit and structured the body as subject and creative act processes that we as a synthesis of organic, cosmic and synthetic elements. Thus the trial proposed highlight corporeity as a time in relation to the imaginary and their creative powers that interaction and change, appear in be like Transfiguration of natural to the figurative principle structure. Here the title of exposure: time, body and transfiguration